The launch of a new generation of the ICSID Rules - Meg Kinnear (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
Five years after launching the most comprehensive review of its procedural rules for resolving international investment disputes, ICSID submitted the amended rules to its Member States for a vote of approval on January 20, 2022. If approved, the amended rules would significantly streamline and modernize ISDS procedure.
Keywords: 330